(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Fine structure energy levels, transition probabilities and oscillator strength for terms belonging to the ground configuration, \(4s^24p^2\) and the first exited odd parity configurations \(4s4p^3\), \(4s^24p5s\) and \(4s^24p4d\) of Ge-I like ions have been calculated using Hartree-Fock method with relativistic correction incorporating large number of interacting configurations \([4s^24p(4f+5p+5g), 4s4p^2(4d+5s), 4p^3(4d+5s)]\). Experimentally reported levels have been compared with theoretical results establishing energy parameters in the first eleven members of the sequence (Ge I-Mo XI). The configuration \(4s^24p4d\) in Rb VI, Sr VII, and \(4s4p^3\) except \(4s4p^3\) \(^5S_2\) level in Ge-I, are not observed yet. A systematic study of Slater parameters in the isoelectronic sequence enabled us to make precise predictions of the missing energy levels belonging to these configurations.